Disparities in the Global Burden of Age-Related Macular Degeneration: An Analysis of Trends from 1990 to 2015. (3rd June 2019) - Wang, Decai; Jiang, Yu; He, Miao; Scheetz, Jane; Wang, Wei
ABSTRACT: Purpose : The purpose of this study was to evaluate the disparities in burden of disease of age-related macular degeneration (AMD) in terms of disability-adjusted life years (DALYs). Method : This is an international, database observational study. The DALYs due to AMD were retrieved from the 2015 Global Burden of Disease study. The human development index (HDI) and gross domestic product (GDP) per capita across countries were obtained from the 2016 Human Development Report and the World Bank. Other related data were obtained from the World Health Organization and United Nations. Results : A total of 195 countries were included in this study. From 1990 to 2015, the AMD-related global DALY numbers, crude DALY rate, and age-standardized DALY rate increased by 147.66%, 78.13%, and 19.3%, respectively. Global DALY rates increased with age and females had higher DALY numbers and rates than males in each age group (all P < 0.01). The age-standardized DALY rate was positively associated with HDI and GDP per capita ( P < 0.001). An analysis by HDI ordering showed substantial socioeconomic inequality, with a concentration index of 0.322 for DALY numbers, 0.472 for crude DALY rate, and 0.142 for age-standardized DALY rate, respectively. The country-wide mean body mass index (BMI), serum cholesterol concentration, alcohol consumption, physical inactivity, percent of cell phone subscribers, and urbanization rate were also significantly associated with age-standardized DALY rate. Four variables (GDP per capita, mean BMI, alcohol consumption, and urbanization rate) explained 36.48% of the variation of age-standardized DALY rate across countries. Conclusion : The global health burden of AMD is constantly increasing, implying more demand for AMD services in the coming decades. Older age, female gender, higher socioeconomic development, physical inactivity, and urbanization rate were related to higher AMD burden. These findings may raise the public concern and awareness of the global impact of AMD burden and are valuable for policy planning.